METHOD OF DETERMINATION OF THERMAL LOAD AIR CONDITIONING SYSTEMS BY MAXIMUM COLD PERFORMANCE RATE (on the example of air conditioning for energy purposes) - Микола Іванович Радченко; Євген Іванович Трушляков; Сергій Анатолійович Кантор; Богдан Сергійович Портной; Анатолій Анатолійович Зубарєв (Авіаційно-космічна техніка та технологія, 2018)
It is justified the necessity of taking into consideration changes in thermal loads on the air conditioning system (heat and moisture treatment of air by cooling it with decreasing temperature and moisture content) in accordance with the current climatic conditions of operation. Since the effect of air cooling depends on the duration of its use and the amount of cold consumption, it is suggested that it be determined by the amount of cold spent per year for air conditioning at the GTU inlet, that is, for annual refrigerating capacity. The example of heat-using air conditioning at the inlet of a gas turbine unite (energy–efficient air conditioning systems) analyzes the annual costs of cooling for cooling ambient air to the temperature of 15 °C by an absorption lithium-bromide chiller and two-stage air cooling: to a temperature of 15 °C in an absorption lithium-bromide chiller and down to temperature 10 °С – in a refrigerant ejector chiller as the stages of a two-stage absorption-ejector chiller, depending on the installed (project) refrigerating capacity of waste heat recovery chiller. It is shown that, based on the varying rate of increment in the annual production of cold (annual refrigeration capacity) due to the change in the thermal load in accordance with current climatic conditions, it is necessary to select such a design thermal load for the air conditioning system (installed refrigeration capacity of chillers), which ensures the achievement of maximum or close to it annual production of cold at a relatively high rate of its increment. It is analyzed the dependence of the increment on the annual refrigerated capacity, relative to the installed refrigeration capacity, on the installed refrigeration capacity, in order to determine the installed refrigeration capacity, which provides the maximum rate of increase in the annual refrigerating capacity (annual production of cold). Based on the results of the research, it is proposed the method for determining the rational thermal load of the air conditioning system (installed – the design refrigeration capacity of the chiller) in accordance with the changing climatic conditions of operation during the year, which provides nearby the maximum annual production of cold at relatively high rates of its growth